Conflict as Property Revisited. Obstacles to Introduce Restorative Justice Procedures and Ways to Overcome Them from the Experience of the Polish Juridical Practice (Archives of Criminology, 2006)
This paper concerns the road Poland is on to introduce restorative justice procedures within its criminal justice system. The author describes the difficulties Poland has already overcome and is still facing. In addition, the paper shows the possible dangers we are not willing to see yet. The restorative justice procedures are introduced in the name of victims. They are aimed at observing the victims' rights and interests within the criminal justice system. Restorative justice is also to bring back the conflicts to their owners. The new developments are aimed at achieving this goal. The author discusses the invisible aspects which, if not diagnosed, named and prevented in time, can steal again the conflict from those most involved in it. It was once stolen by lawyers, judges and prosecutors who officially acted for the victims' good and support. Today, an identical process is possible with mediator taking the lawyers place.